ความสัมพันธ์ระหว่างความรู้สึกเป็นส่วนหนึ่งของสถาบัน ความสุขในการเรียน สภาพแวดล้อมที่เอื้อต่อการเรียนการสอน และผลสัมฤทธิ์ทางการศึกษาของนักศึกษาหลักสูตรพยาบาลศาสตรบัณฑิต - Kraithaworn, Phachongchit; Kittipimpanon, Kamonrat (Nursing Research and Innovation Journal, 2015)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE TH <![endif]--> Abstract: This descriptive study aimed to 1) explore a sense of university belonging, happiness in learning, related environment, and academic achievement and 2) explore the relationship among a sense of university belonging, happiness in learning, related environment, and academic achievement of undergraduate nursing science students. The sample consisted of 564 undergraduate nursing science students who studied in the second to fourth year in 2012. Data were collected by self administrative questionnaires including the demographic questionnaire, related environment, the sense of university belonging scale and the happiness in learning scale. Data were analyzed by using descriptive statistics and Pearson’s correlation. <span style="font-size: 16.0pt; font-family: 'TH SarabunPSK','sans-serif'; mso-fareast-font-family: 'Times New Roman'; color: #231f20; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;"> The findings of the study revealed that most subjects perceived high sense of university belonging, high happiness in learning and having high facilitated environment (74.8, 54.7, and 95.6 percentages, respectively). In addition, 14.6 percentages had high academic achievement (GPA 3.25-4.00). Pearson’s correlation analyses indicated that a sense of university belonging was positive significantly associated with having high facilitated environment, and happiness in learning (r=.48 and r=.60 at level of .01 significance, respectively) but there was no relationship between a sense of university belonging and academic achievement. However, happiness in learning was positive significantly associated with academic achievement and having high facilitated environment (r=.13 and r=.52 at level of .01 significance). <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->